A comprehensive view of intelligent transport systems for urban smart mobility. Issue 1 (2nd January 2017) - Mangiaracina, Riccardo; Perego, Alessandro; Salvadori, Giulio; Tumino, Angela
ABSTRACT: Information accuracy and decision-making speed are of paramount importance in managing today's mobility of goods and people inside the city. Intelligent Transport Systems (ITS) can provide road users with updated information and forecasts on both traffic and weather conditions. The result is a higher efficiency in the use of resources and a better management of physical flows. The purpose of this paper is to conduct an in-depth review on the role of ITS supporting urban Smart Mobility, in order to identify the main gaps in the literature and propose future research streams. In total, 71 papers have been thoroughly analysed: they are mainly focused on technology, with limited attention to value creation. Even though some benefits have been examined, a general lack of quantitative models emerged. Eventually, there is a lack of contributions considering both people and freight transport, even if they are strongly related, especially in an urban environment.